Smith, Pat and Lloyd. A video clip on past gardening practices in Heart's Content. - Wilson, Lisa (2013)
Lloyd and Pat Smith discuss how Lloyd's father grew vegetables and kept animals. Some of this food was for the family, and some of it was sold in the family shop. The photo was taken by Lisa Wilson and shows the site that the Smith family home once stood.